Electrical conductivity of polyaniline (PANI) assisted by anionic surfactant through emulsion polymerization technique. (February 2019) - Manaf, A; Hafizah, M A E; Riyadi, A F; Andreas
Abstract: In this work, Polyaniline (PANI) was synthesized through emulsion polymerization assisted by sodium dodecyl sulfate (SDS) surfactant to investigate effects of surfactant to the electrical conductivity. The amount of SDS used has mol to the total quantity ratio of respectively 0.25%, 0.67%, 1.00%, and 2%. The emulsion aniline polymer obtained from the reaction was confirmed by FTIR. The addition of SDS surfactant as an additional component in the reaction solution, led to the chemical reaction run with a relatively slow rate. It indicated by a relatively long reaction time for an increase in the temperature of reaction solution. The viscosity of the emulsion aniline polymer increased with the addition of SDS. The higher amount of SDS is added, the higher the initial viscosity value of the emulsion. Electrical conductivity value evaluated by Four Point Probe (FPP) showed that the emulsion polymers of aniline doped with 80 ml Perchloric Acid (HQO4 ) have an ohmic relationship between current and voltage from which the conductivity was derived. It was found that the electrical conductivity value of doped PANI assisted by surfactant reached two times higher than that of surfactant-free synthesized PANI. The highest electrical conductivity value obtained is 3.97 S/cm.